Seasonal variation in physical fitness and functional parameters of professional elite soccer players - Silva, J.; Magalhaes, J.; Ascensao, A.; Seabra, A.; Rebelo, A. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Soccer player must be able to perform more than 50 matches over competitive seasons of around 11 months. This high number of competitions in addition to systematic training may impose considerable physiological strain and fatigue to soccer players possibly affecting physical performance over the season. However, the variation of a large group of physical fitness and functional parameters of professional soccer players throughout the entire season has never been assessed, being the purpose of this study. Methods Twenty-two Portuguese elite professional soccer players were evaluated in four occasions throughout the season [prior pre-season (PPS), end pre-season (EPS), mid-season (MID) and end-of-season (EOS)] for counter-movement jump (CMJ), sprint (5 and 30m) agility (T-test), maximal concentric isokinetic knee extensor (KE) and flexor (KF) strength (90ºs-1), and intermittent endurance performance (YYIET2; no YYIET2 data were collected in MID due to the Club match commitments). Results Improvements in 30m sprint test were observed in MID vs. EPS (p<0.01), whereas no change occurred in 5m. CMJ results were higher in EPS vs. PPS, MID and EOS (p<0.05). The performance in T-test improved (p<0.01) in MID and EOS vs. PPS and EPS. No significant changes were found in KE, KF and bilateral leg strength differences (BD) along the season. However, the dominant leg hamstring/quadriceps ratio (H/Q-DL) increased (p<0.05) from MID to PPS. The YYIETL2 performance was higher in EPS (p<0.01) and EOS (p<0.05) than in PPS and decreased from EPS to EOS (p<0.05). Discussion Our results suggest that sprint performance is considerable stable throughout the season. Variations in CMJ performance are in accordance with Clark et al. (2008) but not with Malliou et al. (2003). With the exception of H/Q-DL ratio, players maintain the same levels of KE, KF and BD throughout the season. The increased agility in MID and EOS might be due to possible improvements in soccer-specific coordination levels, allowing an improved ability to stop, start and turn rapidly. The increments in YYIET2 observed in competitive period may be related to improvements in players` endurance-related physiological features as aerobic power (Mohr et al., 2002) and anaerobic threshold (Clark et al., 2008), as well as to the increased ability to repeatedly perform eccentric muscular actions. The decrements in YYIET2 performance from EOS to EPS may be linked with the specificity of competition schedule (eg. high number of games in the second half of season), that is, with the reduction in the time devoted to fitness training and also to the development of chronic fatigue. References Clark N, Edwards AM, Morton R, Butterly, J. (2008). J Sports Sci Med, 7, 157-165. Mohr M, Krustrup P, Bangsbo J. (2002). Med Sci Sports Exerc, 36 (5), 24. Malliou P, Ispirlidis I, Beneka A, Taxildaris K, Godolias G. (2003). Isok Exerc Sci, 11, 165-169.